A low temperature resistant composite material, preparation method and application in negative electrode material of lithium ion battery

By using a low-temperature composite material with a regular pore structure and a high specific surface area and a crosslinked polymer conductive grid structure on the negative electrode of the lithium-ion battery, the problem of insufficient lithium dendrites inhibition ability in a low-temperature environment is solved, and the battery cycle life is extended and the safety is improved.

CN119461335BActive Publication Date: 2025-03-18SHENZHEN EPT BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510066090.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

When the negative electrode of the lithium-ion battery is charged in a low-temperature environment, the growth inhibition ability of lithium dendrites is insufficient, resulting in a decrease in cycle life and an increase in safety risks.

Method used

A benzotriazole compound is used as an organic ligand to combine with zinc ions to prepare a metal organic framework compound with a regular pore structure and a high specific surface area, and a low-temperature resistant composite material with a crosslinking copolymerization reaction with lithium acrylate is formed. The material is coated on the negative electrode of the lithium-ion battery to improve lithium ion transfer and conduction at low temperatures.

Benefits of technology

It effectively inhibits the generation of lithium dendrites, improves the circulation performance and safety of lithium-ion batteries in low temperature environments, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461335B_ABST
    Figure CN119461335B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and in particular to a low temperature resistant composite material, a preparation method and an application in a negative electrode material of a lithium ion battery. The preparation method of the low temperature resistant composite material comprises: 5-chlorobenzotriazole reacts with potassium ferrocyanide to obtain 5-cyano-benzotriazole; 5-cyano-benzotriazole reacts with 3-butenylmagnesium bromide to obtain alkenyl-containing benzotriazole; alkenyl-containing benzotriazole reacts with zinc nitrate to obtain an alkenyl-containing metal organic framework compound; the alkenyl-containing metal organic framework compound undergoes a polymerization cross-linking reaction with lithium acrylate to obtain a cross-linked copolymer; the cross-linked copolymer is calcined and carbonized to obtain a low temperature resistant composite material. When the negative electrode material prepared by the low temperature resistant composite material is applied to a lithium ion battery, the lithium ion battery will not form lithium dendrites when charging in a low temperature environment, and the lithium ion battery has a high cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-temperature resistant composite material, a preparation method and application in negative electrode materials of lithium ion batteries. Background Art

[0002] As a rechargeable battery, lithium-ion batteries mainly rely on the movement of lithium ions between the positive and negative electrodes to work. They have the characteristics of high operating voltage, high energy density, and long cycle life. They have been widely used in mobile phones, laptops, electric vehicles and other fields. Traditional lithium-ion batteries generally use graphite negative electrode materials, which can provide a stable operating voltage for lithium-ion batteries. However, lithium-ion batteries with graphite as negative electrode materials have low specific capacity and cannot meet the requirements of high capacity. Therefore, lithium-ion batteries using metallic lithium as negative electrode materials have gradually attracted attention and application. However, when charging in a low temperature environment, the diffusion resistance of lithium ions in the negative electrode material increases, causing lithium ions to deposit on the surface of the negative electrode to form lithium dendrites, resulting in a decrease in the cycle life of lithium-ion batteries. In addition, the growth of lithium dendrites will puncture the battery diaphragm, causing internal short circuits in the battery and even causing explosions or fires, reducing the safety of lithium-ion batteries.

[0003] Chinese patent CN108258241B discloses a lithium battery negative electrode that utilizes ZIF-8 porous carbon material to inhibit the growth of lithium dendrites. The ZIF-8 zeolite imidazolate skeleton material is prepared by reacting zinc nitrate with 2-methylimidazole. The ZIF-8 zeolite imidazolate skeleton material is carbonized, pickled and coated on the surface of a battery negative electrode lithium sheet to obtain a battery negative electrode. The regular pore structure and high specific surface area of ​​the ZIF-8 porous carbon material are utilized to inhibit the growth of lithium dendrites during battery charging. However, the ability to inhibit the growth of lithium dendrites of the negative electrode when the battery negative electrode is charged in a low temperature environment needs to be improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a low-temperature resistant composite material to solve the problem in the prior art that the ability of the negative electrode of a lithium ion battery to suppress the growth of lithium dendrites when charged in a low-temperature environment needs to be improved.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a low-temperature resistant composite material comprises the following steps:

[0007] Step 1, adding 5-chlorobenzotriazole, cuprous chloride, cuprous bromide and potassium ferrocyanide to N-methylpyrrolidone for reaction, and cooling after the reaction to obtain a reaction mixture 1, and separating and purifying the reaction mixture 1 to obtain 5-cyano-benzotriazole;

[0008] Step 2: Add 5-cyano-benzotriazole into tetrahydrofuran, stir and dissolve to obtain a 5-cyano-benzotriazole solution;

[0009] Add 3-butenylmagnesium bromide to tetrahydrofuran, stir and dissolve, to obtain a 3-butenylmagnesium bromide solution;

[0010] The 5-cyano-benzotriazole solution is added dropwise to the 3-butenylmagnesium bromide solution, and after the addition is complete, the mixture is reacted. After the reaction is complete, the mixture is cooled to obtain a reaction mixture 2, and the reaction mixture 2 is separated and purified to obtain an alkenyl-containing benzotriazole;

[0011] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, stirring for reaction, aging the emulsion obtained by the reaction, centrifuging, washing, and drying to obtain an alkenyl-containing metal organic framework compound;

[0012] Step 4: adding an alkenyl-containing metal organic framework compound and an initiator into dimethyl sulfoxide, and dispersing by ultrasonication to obtain a solution A;

[0013] Add lithium acrylate and initiator into dimethyl sulfoxide and disperse by ultrasonic to obtain solution B;

[0014] Add solution B dropwise to solution A, react after the addition is complete, centrifuge, wash, and dry to obtain a cross-linked copolymer;

[0015] Step 5: calcining and carbonizing the cross-linked copolymer, and cooling after calcination to obtain a low-temperature resistant composite material.

[0016] Preferably, in the step 1, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide and potassium ferrocyanide is 1:(0.5-0.65):(0.1-0.2):(0.2-0.35), the amount of N-methylpyrrolidone added is 8-12 times the mass of 5-chlorobenzotriazole, and the reaction conditions are stirring the reaction at a temperature of 150-170° C. for 6-10 hours under the protection of an inert gas.

[0017] Preferably, the cooling comprises cooling to room temperature under the protection of an inert gas.

[0018] Preferably, the separation and purification comprises adding a diethyl ether / water mixture to the reaction mixture 1, stirring, separating the layers, taking the organic phase, further extracting the aqueous phase with diethyl ether, combining the organic phases, and drying with anhydrous sodium sulfate;

[0019] The amount of the ether / water mixture added is 6-10 times the mass of N-methylpyrrolidone, and the ether / water mixture is prepared by mixing ether and deionized water in a mass ratio of 4:1.

[0020] Preferably, the inert gas comprises nitrogen.

[0021] Preferably, in the step 2: the mass ratio of 3-butenylmagnesium bromide solution to 5-cyano-benzotriazole solution is (7.5-9.5):(5.6-7.6), and the reaction conditions are stirring the reaction at the first set temperature for 20-40 minutes, heating to the second set temperature, and reflux reaction at the second set temperature for 1-2 hours; the first set temperature is 70-80°C, and the second set temperature is 100-110°C.

[0022] Preferably, in the step 2, in the 5-cyano-benzotriazole solution, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:(6-8); in the 3-butenylmagnesium bromide solution, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:(4-6).

[0023] Preferably, the separation and purification comprises adding 0.5 times the mass of glacial hydrochloric acid of the reaction mixture 2 to the reaction mixture 2, stirring, layering, taking the organic phase, washing the organic phase with a 5wt% NaHCO3 aqueous solution, adding anhydrous sodium sulfate to dry, and removing the solvent tetrahydrofuran by rotary evaporation at a temperature of 50°C;

[0024] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C.

[0025] Preferably, in the step three, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:(4-4.4), the amount of ethanol added is 10-15 times the mass of zinc nitrate hexahydrate, the stirring reaction conditions are stirring the reaction at room temperature and a stirring speed of 100-200 r / min for 6-10 hours, and the aging conditions are standing and aging at room temperature for 20-30 hours.

[0026] Preferably, in the step 4: when preparing solution A, the mass ratio of the alkenyl-containing metal organic framework compound, the initiator, and dimethyl sulfoxide is 20.1:(3-5):(1000-1500);

[0027] When preparing solution B, the mass ratio of lithium acrylate, initiator, and dimethyl sulfoxide is 7.8:(0.5-1):(250-300);

[0028] When preparing the cross-linked copolymer, the molar ratio of the metal organic framework compound containing alkenyl in solution A to the lithium acrylate in solution B is 1:(20-30);

[0029] The reaction conditions are as follows: under the protection of an inert gas, stirring the reaction at 60-80° C. for 10-20 h.

[0030] Preferably, when preparing solution A and solution B, the initiator used is the same;

[0031] The initiator includes azobisisobutyronitrile.

[0032] Preferably, the inert gas comprises nitrogen.

[0033] Preferably, in step 5: the calcination and carbonization conditions are calcination at 550-700° C. for 4-6 hours under a nitrogen atmosphere.

[0034] The invention also discloses a low-temperature resistant composite material prepared by the preparation method of the low-temperature resistant composite material as mentioned above.

[0035] Preferably, the low-temperature resistant composite material as described above is used in negative electrode materials for lithium-ion batteries.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] In the present invention, a benzotriazole compound is used as an organic ligand and a zinc ion is used as an inorganic metal center to prepare a metal organic framework compound. The metal organic framework compound has a regular pore structure and a high specific surface area. The high specific surface area of ​​the three-dimensional framework can reduce the local space current density, homogenize the electric field and inhibit the accumulation of charges, thereby achieving uniform deposition of lithium ions without the generation of lithium dendrites.

[0038] The invention adopts 5-chlorobenzotriazole as an organic ligand, and the 5-chlorobenzotriazole is subjected to a modification treatment: the 5-chlorobenzotriazole is introduced with a nitrile group by reacting with potassium ferrocyanide, and then an alkenyl group is introduced into the benzotriazole molecule by reacting with a cyano group and a Grignard reagent 3-butenylmagnesium bromide to obtain an alkenyl-containing benzotriazole, and the benzotriazole reacts with zinc ions to obtain an alkenyl-containing metal organic framework compound; lithium acrylate has high ion conductivity, the alkenyl-containing metal organic framework compound and lithium acrylate undergo a cross-linking copolymerization reaction under the action of an initiator, and the cross-linked copolymer is subjected to calcined carbon. The low-temperature resistant composite material is formed by coating the low-temperature resistant composite material with a cross-linked polymer conductive grid structure on a metal lithium sheet to prepare a lithium ion battery negative electrode, which can reduce the charge transfer impedance and improve the interfacial lithium ion transfer at low temperatures. Lithium ions are directly deposited on the cross-linked polymer conductive grid to form a flat lithium metal surface, avoiding the formation of lithium dendrites without hindering lithium ion conduction, achieving rapid lithium ion transmission, and improving the low-temperature charging performance of lithium ion batteries, thereby increasing the cycle life of lithium ion batteries. In addition, inhibiting the formation of lithium dendrites can also reduce the safety hazards of lithium ion batteries in use. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a process flow chart for preparing the low-temperature resistant composite material of the present invention;

[0040] Figure 2 It is a line graph showing the test results of low-temperature cycle performance of lithium-ion batteries when the negative electrode made of the low-temperature resistant composite materials prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention is applied to lithium-ion batteries. DETAILED DESCRIPTION

[0041] Example 1

[0042] This embodiment discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0043] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.5:0.1:0.2, the amount of N-methylpyrrolidone added is 8 times the mass of 5-chlorobenzotriazole, under nitrogen protection, at a temperature of 150°C, the reaction is stirred for 10 hours, and the stirring speed is 150r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, ether / water mixed solution is added to the reaction mixture 1, stirred, layered, the organic phase is taken, the aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by reduced pressure distillation at room temperature to obtain 5-cyano-benzotriazole;

[0044] The amount of the ether / water mixture added is 6 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0045] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:6, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0046] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:4, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0047] The 5-cyano-benzotriazole solution is added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution is 7.5:5.6, the 5-cyano-benzotriazole solution is added dropwise for 30 minutes, after the addition is completed, the mixture is stirred at 70°C for 40 minutes, the stirring speed is 150r / min, the temperature is raised to 100°C, and the mixture is refluxed at 100°C for 2 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a reaction mixture 2, 0.5 times the mass of the reaction mixture 2 is added with glacial hydrochloric acid, the mixture is stirred, the mixture is separated, the organic phase is taken, the organic phase is washed with a 5wt% NaHCO3 aqueous solution, anhydrous sodium sulfate is added for drying, tetrahydrofuran is removed by rotary evaporation at 50°C, and an alkenyl-containing benzotriazole is obtained;

[0048] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0049] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4, the amount of ethanol added is 10 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature at a stirring speed of 100 r / min for 10 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 20 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50° C. for 24 hours to obtain an alkenyl-containing metal organic framework compound;

[0050] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:3:1000, and ultrasonically dispersing the mixture at a frequency of 50 kHz for 30 minutes to obtain a solution A;

[0051] Add lithium acrylate and azobisisobutyronitrile to dimethyl sulfoxide, the mass ratio of lithium acrylate, azobisisobutyronitrile and dimethyl sulfoxide is 7.8:0.5:250, and disperse by ultrasound at a frequency of 50 kHz for 30 minutes to obtain solution B;

[0052] Solution B was added dropwise to solution A, the molar ratio of the alkenyl-containing metal organic framework compound in solution A to the lithium acrylate in solution B was 1:20, and the dropping time of solution B was 30 min. After the dropping was completed, the mixture was stirred and reacted at 60° C. for 20 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was washed with ethanol 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a cross-linked copolymer;

[0053] Step 5: calcine the cross-linked copolymer at 550°C for 6 hours under a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, cool it naturally to room temperature to obtain a low-temperature resistant composite material.

[0054] Example 2

[0055] This embodiment discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0056] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.65:0.2:0.35, and the amount of N-methylpyrrolidone added is 12 times the mass of 5-chlorobenzotriazole. Under nitrogen protection, the reaction is stirred at 170°C for 6 hours at a stirring speed of 150 r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, and an ether / water mixture is added to the reaction mixture 1, stirred, layered, and the organic phase is taken. The aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by rotary evaporation at room temperature to obtain 5-cyano-benzotriazole;

[0057] The amount of the ether / water mixture added is 10 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0058] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:8, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0059] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:6, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0060] The 5-cyano-benzotriazole solution is added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution is 9.5:7.6, and the dropping time of the 5-cyano-benzotriazole solution is 30 minutes. After the dropwise addition is completed, the reaction is stirred at 80°C for 20 minutes at a stirring speed of 150r / min, the temperature is raised to 110°C, and the reaction is refluxed at 110°C for 1 hour. After the reaction is completed, the reaction mixture is cooled to room temperature to obtain a reaction mixture 2, and 0.5 times the mass of the reaction mixture 2 is added to the reaction mixture 2. The mixture is stirred, separated, and the organic phase is taken. The organic phase is washed with a 5wt% NaHCO3 aqueous solution, and then anhydrous sodium sulfate is added to dry it. The tetrahydrofuran is removed by rotary evaporation at 50°C to obtain an alkenyl-containing benzotriazole;

[0061] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0062] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4.4, the amount of ethanol added is 15 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature and a stirring speed of 200 r / min for 6 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 30 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50° C. for 24 hours to obtain an alkenyl-containing metal organic framework compound;

[0063] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:5:1500, and ultrasonically dispersing the mixture at a frequency of 50 kHz for 30 min to obtain a solution A;

[0064] Add lithium acrylate and azobisisobutyronitrile to dimethyl sulfoxide, the mass ratio of lithium acrylate, azobisisobutyronitrile and dimethyl sulfoxide is 7.8:1:300, and disperse them ultrasonically at a frequency of 50 kHz for 30 minutes to obtain solution B;

[0065] Solution B was added dropwise to solution A, the molar ratio of the alkenyl-containing metal organic framework compound in solution A to the lithium acrylate in solution B was 1:30, and the dropping time of solution B was 30 min. After the dropping was completed, the mixture was stirred and reacted at 80° C. for 10 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was washed with ethanol 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a cross-linked copolymer;

[0066] Step 5: calcining the cross-linked copolymer at 700°C for 4 hours in a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, the copolymer is naturally cooled to room temperature to obtain a low-temperature resistant composite material.

[0067] Example 3

[0068] This embodiment discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0069] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.54:0.12:0.23, the amount of N-methylpyrrolidone added is 10 times the mass of 5-chlorobenzotriazole, and the reaction is stirred at 160°C for 8h under nitrogen protection, and the stirring speed is 150r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, and an ether / water mixture is added to the reaction mixture 1, stirred, layered, and the organic phase is taken. The aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by rotary evaporation at room temperature to obtain 5-cyano-benzotriazole;

[0070] The amount of the ether / water mixture added is 8 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0071] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:6.5, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0072] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:4.5, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0073] The 5-cyano-benzotriazole solution was added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution was 8:6.1, and the dropping time of the 5-cyano-benzotriazole solution was 30 min. After the dropping was completed, the mixture was stirred at 75°C for 30 min, the stirring speed was 150 r / min, the temperature was raised to 105°C, and the mixture was refluxed at 105°C for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a reaction mixture 2, 0.5 times the mass of the reaction mixture 2 was added with glacial hydrochloric acid, the mixture was stirred, the mixture was separated, and the organic phase was taken. The organic phase was washed with a 5wt% NaHCO3 aqueous solution, and then dried with anhydrous sodium sulfate. The tetrahydrofuran was removed by rotary evaporation at 50°C to obtain an alkenyl-containing benzotriazole.

[0074] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0075] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4.1, the amount of ethanol added is 12 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature and a stirring speed of 150 r / min for 8 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 25 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50° C. for 24 hours to obtain an alkenyl-containing metal organic framework compound;

[0076] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:3.5:1100, and ultrasonically dispersing the mixture at a frequency of 50 kHz for 30 min to obtain a solution A;

[0077] Add lithium acrylate and azobisisobutyronitrile to dimethyl sulfoxide, the mass ratio of lithium acrylate, azobisisobutyronitrile and dimethyl sulfoxide is 7.8:0.6:260, and disperse by ultrasound at a frequency of 50 kHz for 30 minutes to obtain solution B;

[0078] Solution B was added dropwise to solution A, the molar ratio of the alkenyl-containing metal organic framework compound in solution A to the lithium acrylate in solution B was 1:22, and the dropping time of solution B was 30 min. After the dropping was completed, the mixture was stirred and reacted at 70° C. for 15 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was washed with ethanol 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a cross-linked copolymer;

[0079] Step 5: calcining the cross-linked copolymer at 600°C for 5 hours in a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, the copolymer is naturally cooled to room temperature to obtain a low-temperature resistant composite material.

[0080] Example 4

[0081] This embodiment discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0082] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.58:0.15:0.28, and the amount of N-methylpyrrolidone added is 10 times the mass of 5-chlorobenzotriazole. Under nitrogen protection, the reaction is stirred at 160°C for 8h, and the stirring speed is 150r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, and an ether / water mixture is added to the reaction mixture 1, stirred, layered, and the organic phase is taken. The aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by rotary evaporation at room temperature to obtain 5-cyano-benzotriazole;

[0083] The amount of the ether / water mixture added is 8 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0084] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:7, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0085] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:5, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0086] The 5-cyano-benzotriazole solution was added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution was 8.5:6.6, and the dropping time of the 5-cyano-benzotriazole solution was 30 min. After the dropping was completed, the mixture was stirred at 75°C for 30 min, the stirring speed was 150 r / min, the temperature was raised to 105°C, and the mixture was refluxed at 105°C for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a reaction mixture 2, 0.5 times the mass of the reaction mixture 2 was added with glacial hydrochloric acid, the mixture was stirred, the mixture was separated, and the organic phase was taken. The organic phase was washed with a 5wt% NaHCO3 aqueous solution, anhydrous sodium sulfate was added for drying, and tetrahydrofuran was removed by rotary evaporation at 50°C to obtain an alkenyl-containing benzotriazole;

[0087] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0088] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4.2, the amount of ethanol added is 12.5 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature and a stirring speed of 150 r / min for 8 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 25 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50° C. for 24 hours to obtain an alkenyl-containing metal organic framework compound;

[0089] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:4:1250, and ultrasonically dispersing at a frequency of 50 kHz for 30 minutes to obtain a solution A;

[0090] Add lithium acrylate and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of lithium acrylate, azobisisobutyronitrile and dimethyl sulfoxide is 7.8:0.75:275, and disperse by ultrasound at a frequency of 50 kHz for 30 minutes to obtain solution B;

[0091] Solution B was added dropwise to solution A, the molar ratio of the alkenyl-containing metal organic framework compound in solution A to the lithium acrylate in solution B was 1:25, and the dropping time of solution B was 30 min. After the dropping was completed, the mixture was stirred and reacted at 70° C. for 15 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was washed with ethanol 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a cross-linked copolymer;

[0092] Step 5: calcining the cross-linked copolymer at 600°C for 5 hours in a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, the copolymer is naturally cooled to room temperature to obtain a low-temperature resistant composite material.

[0093] Example 5

[0094] This embodiment discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0095] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.62:0.18:0.32, and the amount of N-methylpyrrolidone added is 10 times the mass of 5-chlorobenzotriazole. Under nitrogen protection, the reaction is stirred at 160°C for 8h, and the stirring speed is 150r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, and an ether / water mixture is added to the reaction mixture 1, stirred, layered, and the organic phase is taken. The aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by rotary evaporation at room temperature to obtain 5-cyano-benzotriazole;

[0096] The amount of the ether / water mixture added is 8 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0097] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:7.5, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0098] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:5.5, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0099] The 5-cyano-benzotriazole solution was added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution was 9:7.1, and the dropping time of the 5-cyano-benzotriazole solution was 30 min. After the dropping was completed, the mixture was stirred at 75°C for 30 min, the stirring speed was 150 r / min, the temperature was raised to 105°C, and the mixture was refluxed at 105°C for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a reaction mixture 2, 0.5 times the mass of the reaction mixture 2 was added with glacial hydrochloric acid, the mixture was stirred, the mixture was separated, and the organic phase was taken. The organic phase was washed with a 5wt% NaHCO3 aqueous solution, and then dried with anhydrous sodium sulfate. The tetrahydrofuran was removed by rotary evaporation at 50°C to obtain an alkenyl-containing benzotriazole.

[0100] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0101] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4.3, the amount of ethanol added is 14 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature and a stirring speed of 150r / min for 8h, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 25h, centrifuging at a speed of 3000r / min for 10min, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50°C for 24h to obtain an alkenyl-containing metal organic framework compound;

[0102] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:4.5:1400, and ultrasonically dispersing the mixture at a frequency of 50 kHz for 30 min to obtain a solution A;

[0103] Add lithium acrylate and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of lithium acrylate, azobisisobutyronitrile and dimethyl sulfoxide is 7.8:0.9:290, and disperse by ultrasound at a frequency of 50 kHz for 30 minutes to obtain solution B;

[0104] Solution B was added dropwise to solution A, the molar ratio of the alkenyl-containing metal organic framework compound in solution A to the lithium acrylate in solution B was 1:28, and the dropping time of solution B was 30 min. After the dropping was completed, the mixture was stirred and reacted at 70° C. for 15 h under nitrogen protection. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was washed with ethanol 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a cross-linked copolymer;

[0105] Step 5: calcining the cross-linked copolymer at 600°C for 5 hours in a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, the copolymer is naturally cooled to room temperature to obtain a low-temperature resistant composite material.

[0106] Comparative Example 1

[0107] This comparative example discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0108] Step 1, 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide are added to N-methylpyrrolidone, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide, and potassium ferrocyanide is 1:0.5:0.1:0.2, and the amount of N-methylpyrrolidone added is 8 times the mass of 5-chlorobenzotriazole. Under nitrogen protection, the reaction is stirred at 150°C for 10 hours at a stirring speed of 150 r / min. After the reaction is completed, it is cooled to room temperature under nitrogen protection to obtain a reaction mixture 1, an ether / water mixture is added to the reaction mixture 1, stirred, layered, the organic phase is taken, the aqueous phase is continuously extracted with ether, the organic phases are combined, dried over anhydrous sodium sulfate, and the ether is removed by rotary evaporation at room temperature to obtain 5-cyano-benzotriazole;

[0109] The amount of the ether / water mixture added is 6 times the mass of N-methylpyrrolidone, and the ether / water mixture is a mixture of ether and deionized water in a mass ratio of 4:1;

[0110] Step 2, adding 5-cyano-benzotriazole to tetrahydrofuran, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:6, stirring and dissolving to obtain a 5-cyano-benzotriazole solution;

[0111] Add 3-butenylmagnesium bromide to tetrahydrofuran, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:4, stir and dissolve to obtain a 3-butenylmagnesium bromide solution;

[0112] The 5-cyano-benzotriazole solution is added dropwise to the 3-butenylmagnesium bromide solution, the mass ratio of the 3-butenylmagnesium bromide solution to the 5-cyano-benzotriazole solution is 7.5:5.6, the 5-cyano-benzotriazole solution is added dropwise for 30 minutes, after the addition is completed, the mixture is stirred at 70°C for 40 minutes, the stirring speed is 150r / min, the temperature is raised to 100°C, and the mixture is refluxed at 100°C for 2 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a reaction mixture 2, 0.5 times the mass of the reaction mixture 2 is added with glacial hydrochloric acid, the mixture is stirred, the mixture is separated, the organic phase is taken, the organic phase is washed with a 5wt% NaHCO3 aqueous solution, anhydrous sodium sulfate is added for drying, tetrahydrofuran is removed by rotary evaporation at 50°C, and an alkenyl-containing benzotriazole is obtained;

[0113] Wherein, glacial hydrochloric acid is 20wt% hydrochloric acid at 0°C;

[0114] Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:4, the amount of ethanol added is 10 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature at a stirring speed of 100 r / min for 10 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 20 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50° C. for 24 hours to obtain an alkenyl-containing metal organic framework compound;

[0115] Step 4: adding an alkenyl-containing metal organic framework compound and azobisisobutyronitrile to dimethyl sulfoxide, wherein the mass ratio of the alkenyl-containing metal organic framework compound, azobisisobutyronitrile and dimethyl sulfoxide is 20.1:3:1000, and ultrasonically dispersing the mixture at a frequency of 50 kHz for 30 minutes, stirring the mixture under nitrogen protection at a temperature of 60° C. for 20 hours, and centrifuging the mixture after the reaction is completed. The centrifugal precipitate is washed three times with ethanol and dried in a vacuum drying oven at 50° C. for 24 hours to obtain a cross-linked copolymer;

[0116] Step 5: calcine the cross-linked copolymer at 550°C for 6 hours under a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, cool it naturally to room temperature to obtain a low-temperature resistant composite material.

[0117] Comparative Example 2

[0118] This comparative example discloses a method for preparing a low-temperature resistant composite material, comprising the following steps:

[0119] Step 1, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding 5-chlorobenzotriazole to the zinc nitrate solution, the molar ratio of zinc nitrate hexahydrate to 5-chlorobenzotriazole is 1:4, the amount of ethanol added is 10 times the mass of zinc nitrate hexahydrate, stirring and reacting at room temperature at a stirring speed of 100 r / min for 10 hours, leaving the emulsion obtained by the reaction to stand for aging at room temperature for 20 hours, centrifuging at a speed of 3000 r / min for 10 minutes, washing the centrifugal precipitate with ethanol 3 times, and drying it in a vacuum drying oven at 50°C for 24 hours to obtain a metal organic framework compound;

[0120] Step 2: calcine the metal organic framework compound at 550°C for 6 hours in a nitrogen atmosphere with a heating rate of 5°C / min. After calcination, cool it naturally to room temperature to obtain a low-temperature resistant composite material.

[0121] In the above embodiments and comparative examples: 5-chlorobenzotriazole was purchased from Ningbo Yinuo Chemical Co., Ltd., CAS No.: 94-97-3; cuprous chloride was purchased from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd., grade: analytical grade AR, CAS No.: 7758-89-6; cuprous bromide was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., grade: analytical grade AR, CAS No.: 7787-70-4; potassium ferrocyanide was purchased from Wuxi Yatai United Chemical Co., Ltd., grade: analytical grade AR, CAS No.: 14459-95 -1; N-methylpyrrolidone was purchased from Hubei Hongfuda Biotechnology Co., Ltd., purity specification: 99%, CAS number: 872-50-4; 3-butenylmagnesium bromide was purchased from Tesco Chemical (Hubei) Co., Ltd., CAS number: 7103-09-5; zinc nitrate hexahydrate was purchased from Sinopharm Chemical Reagent Co., Ltd., grade: analytical grade AR, CAS number: 10196-18-6; lithium acrylate was purchased from Shanghai Hansi Chemical Co., Ltd., purity specification: ≥98%, CAS number: 13270-28-5.

[0122] Test example

[0123] The performance test of the low-temperature resistant composite materials prepared in Examples 1-5 and Comparative Examples 1-2 was performed: the low-temperature resistant composite materials, polyvinylidene fluoride, and N-methylpyrrolidone prepared in Examples 1-5 and Comparative Examples 1-2 were mixed, and the mass ratio of the low-temperature resistant composite materials to polyvinylidene fluoride was 10:1. The mixture was ground to obtain a negative electrode slurry, and the solid content of the negative electrode slurry was 50%. A metal lithium sheet with a thickness of 1 mm and a diameter of 15 mm was taken as the negative electrode sheet of the lithium ion battery. The negative electrode slurry was coated on the surface of the metal lithium sheet with a coating thickness of 120 μm, and the sheet was placed in a glove box filled with nitrogen and free of water to dry naturally to obtain the negative electrode of the lithium ion battery. The commercial phosphorus The lithium iron phosphate active material, acetylene black, polyvinylidene fluoride, and N-methyl pyrrolidone are mixed, the mass ratio of lithium iron phosphate active material, acetylene black and polyvinylidene fluoride is 80:10:10, and the positive electrode slurry is obtained by grinding. The solid content of the positive electrode slurry is 50%. The positive electrode slurry is coated on an aluminum foil with a thickness of 1 mm, and the coating thickness is 200 μm. It is vacuum dried at 120°C for 12 hours, and after natural cooling, it is cut into discs with a diameter of 15 cm by a punching machine to obtain a lithium ion positive electrode; 1M (trifluoromethanesulfonyl) lithium imide is dissolved in 1,3-dioxolane / 1,2-dimethoxyethane with a volume ratio of 1:1 as the electrolyte, Celgard 2325 was used as the separator, and the negative electrode, positive electrode, electrolyte and separator were assembled into a lithium-ion battery. The low-temperature cycle performance test of the lithium-ion battery was carried out: at a temperature of -15°C, 0.5C charging, 1C discharging, and a charge and discharge cut-off voltage of 2.5-4.2V. The capacity retention rate after 150 cycles was measured. The test results are shown in Table 1:

[0124] Table 1

[0125] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Capacity retention rate (%) 92.6 91.9 92.2 92.1 92.4 91.3 83.8

[0126] As shown in Table 1, when the negative electrode prepared by the low-temperature resistant composite material prepared by the present invention is applied to a lithium-ion battery, the lithium-ion battery still has an excellent cycle life, and still has a very high capacity retention rate even after multiple cycles in a low-temperature environment. The low-temperature resistant composite material uses benzotriazole compounds as organic ligands and zinc ions as inorganic metal centers to prepare metal organic framework compounds. The benzotriazole compounds are modified, and the introduced olefin groups undergo cross-linking copolymerization with lithium acrylate under the action of an initiator. The cross-linked copolymer is calcined and carbonized to form a low-temperature resistant composite material with a cross-linked polymer conductive grid structure, which can reduce charge transfer impedance and improve interfacial lithium ion transfer at low temperatures. Lithium ions are directly deposited on the cross-linked polymer conductive grid to form a flat lithium metal surface, avoid the formation of lithium dendrites, and do not hinder lithium ion conduction, thereby achieving rapid transmission of lithium ions and improving the low-temperature performance of lithium-ion batteries. Compared with Example 1, when preparing the low-temperature resistant composite material in Comparative Example 1, the raw materials for preparing the cross-linked copolymer do not contain lithium acrylate, the interfacial lithium ion transfer ability at low temperatures is reduced, and the low-temperature cycle performance of the lithium ion battery is reduced; compared with Comparative Example 1, the metal organic framework compound in Comparative Example 2 has not undergone copolymerization reaction and cannot form a cross-linked polymer conductive grid, and the low-temperature cycle performance of the lithium ion battery is further reduced.

[0127] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a low-temperature resistant composite material, characterized in that: The following steps are involved: Step 1, adding 5-chlorobenzotriazole, cuprous chloride, cuprous bromide and potassium ferrocyanide to N-methylpyrrolidone for reaction, and cooling after the reaction to obtain a reaction mixture 1, and separating and purifying the reaction mixture 1 to obtain 5-cyano-benzotriazole; Step 2: Add 5-cyano-benzotriazole into tetrahydrofuran, stir and dissolve to obtain a 5-cyano-benzotriazole solution; Add 3-butenylmagnesium bromide to tetrahydrofuran, stir and dissolve, to obtain a 3-butenylmagnesium bromide solution; The 5-cyano-benzotriazole solution is added dropwise to the 3-butenylmagnesium bromide solution, and after the addition is complete, the mixture is reacted. After the reaction is complete, the mixture is cooled to obtain a reaction mixture 2, and the reaction mixture 2 is separated and purified to obtain an alkenyl-containing benzotriazole; Step 3, dissolving zinc nitrate hexahydrate in ethanol to obtain a zinc nitrate solution; adding alkenyl-containing benzotriazole to the zinc nitrate solution, stirring for reaction, aging the emulsion obtained by the reaction, centrifuging, washing, and drying to obtain an alkenyl-containing metal organic framework compound; Step 4: adding an alkenyl-containing metal organic framework compound and an initiator into dimethyl sulfoxide, and dispersing by ultrasonication to obtain a solution A; Add lithium acrylate and initiator into dimethyl sulfoxide, and disperse by ultrasonic to obtain solution B; Add solution B dropwise to solution A, react after the addition is complete, centrifuge, wash, and dry to obtain a cross-linked copolymer; Step 5: calcining and carbonizing the cross-linked copolymer, and cooling after calcination to obtain a low-temperature resistant composite material.

2. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 1, the molar ratio of 5-chlorobenzotriazole, cuprous chloride, cuprous bromide and potassium ferrocyanide is 1:(0.5-0.65):(0.1-0.2):(0.2-0.35), the amount of N-methylpyrrolidone added is 8-12 times the mass of 5-chlorobenzotriazole, and the reaction conditions are stirring the reaction at a temperature of 150-170° C. for 6-10 hours under the protection of an inert gas.

3. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 2, the mass ratio of the 3-butenyl magnesium bromide solution to the 5-cyano-benzotriazole solution is (7.5-9.5): (5.6-7.6), and the reaction conditions are stirring the reaction at the first set temperature for 20-40 minutes, heating to the second set temperature, and reflux reaction at the second set temperature for 1-2 hours; The first set temperature is 70-80°C, and the second set temperature is 100-110°C.

4. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 2, in the 5-cyano-benzotriazole solution, the mass ratio of 5-cyano-benzotriazole to tetrahydrofuran is 1.5:(6-8); in the 3-butenylmagnesium bromide solution, the mass ratio of 3-butenylmagnesium bromide to tetrahydrofuran is 1.6:(4-6).

5. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 3, the molar ratio of zinc nitrate hexahydrate to alkenyl-containing benzotriazole is 1:(4-4.4), the amount of ethanol added is 10-15 times the mass of zinc nitrate hexahydrate, the stirring reaction is carried out at room temperature and a stirring speed of 100-200 r / min for 6-10 hours, and the aging condition is to stand and age for 20-30 hours at room temperature.

6. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 4: when preparing the cross-linked copolymer, the molar ratio of the metal organic framework compound containing alkenyl in solution A to the lithium acrylate in solution B is 1:(20-30); The reaction conditions are as follows: under the protection of an inert gas, stirring the reaction at 60-80° C. for 10-20 h.

7. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 4: when preparing solution A, the mass ratio of the alkenyl-containing metal organic framework compound, the initiator, and dimethyl sulfoxide is 20.1:(3-5):(1000-1500); When preparing solution B, the mass ratio of lithium acrylate, initiator and dimethyl sulfoxide is 7.8:(0.5-1):(250-300).

8. The method for preparing a low-temperature resistant composite material according to claim 1, characterized in that: In the step 5, the calcination and carbonization conditions are calcination at 550-700° C. for 4-6 hours in a nitrogen atmosphere.

9. A low-temperature resistant composite material prepared by the method for preparing a low-temperature resistant composite material according to any one of claims 1 to 8.

10. Use of the low-temperature resistant composite material according to claim 9 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • A lithium battery anode using ZIF-8 porous carbon material to suppress lithium dendrite growth

    CN108258241B

  • Silicon-based negative electrode material with ultralow temperature and high cycle stability and lithium ion battery thereof

    CN117476902A

  • Low-temperature-resistant sodium-ion battery hard carbon negative electrode material and preparation method thereof

    CN118263428A